The Effect of Lipoic Acid on Macro and Trace Metal Levels in Living Tissues Exposed to Oxidative Stress - Ciftci, Harun; Bakal, Unal (Bentham Science Publ Ltd, 2009)
Environmental pollution resulting from fast-paced industrialization, various chemicals used in agriculture, additives in food, smoking and use of alcohol, radiation, some viruses and poor dietary habits all have currently increased the incidence and types of cancer. Polycyclic hydrocarbons are an example of this type of carcinogens. Living things are exposed to this free radical-increasing substance due to various reasons. Oxidative stress caused by reactive oxygen species has an important place in the etiology of cancer, which develops in relation to many factors. Injury caused by cancer in the organism may affect other organs, as well as the tumors organs and tissues. In addition, it is known that some changes take place in the content of macro and trace elements due to cancer in the organism. Our study is intended to explore the protective role of alpha-lipoic acid, which has antioxidant characteristics in living tissues exposed to oxidative stress, in the macro and trace element levels.
Keywords: Cancer; 7, 12-dimethylbenz-[a]anthracene; Lipoic acid; Trace element; DMBA; Oxidative stress